Submerged at the bottom of an ocean of air: Atmospheric Thought in Jean Epstein's The Tempest and Helena Wittman's Drift - Gattás Vargas, Maia (2025)
Fil: Gattás Vargas, Maia. Universidad Nacional de Río Negro. Instituto de Estudios en Ciencia, Tecnología, Cultura y Desarrollo. Río Negro; Argentina.